OPTIMALISASI DIGITAL MARKETING UNTUK MENUMBUHKAN MINAT WIRAUSAHA PADA WARGA PERUMAHAN GRAND VIONA KURIPAN - Ivantan; Ariyanto, Aris; Yusuf, Ade (Abdi Jurnal Publikasi, 2024)
Becoming a successful entrepreneur or entrepreneur is everyone's dream. To grow entrepreneurial interest requires special skills. With an entrepreneurial spirit, a person will be motivated to always be productive and carry out innovations, to create more profitable business opportunities. The aim of implementing this Community Service activity is to provide education on how to foster entrepreneurial interest through optimizing digital marketing. The methods that will be used to achieve the goals are lectures, discussions, examples and questions and answers, as well as mentoring for community members. The long-term results and goals of this program are to create more productive community members through online business entrepreneurship.